ANALISA KERJA KOMPRESOR TERHADAP PENGGUNAAN REFRIGERAN R12 DAN HIDROKARBON JENIS PIB (PROPANE ISO BUTANE) - Syahrani, Awal (MEKTEK, 2006)
Good Refrigeran and used many up to last some years is the refrigeran from halokarbon group, specially CFC ( Chloroflorocarbon) And HCFC ( Hydrochloroflorocarbon). But in the year 1974 Rowland and Molina draught tell its hypothesizing which express that chlorine the refrigeran have potency ozone layer coat ( ODP = Ozone Depletion Potential) so that can destroy ozone coat as well as owning global(GWP warm-up potency = Global of Warming Potential). Therefore writer make the research of efect use the R-12 refrigeran and Hydrocarbon to kompresor activity by using Coefisien Of Performance parameter ( COP)andEffisiensi from refrigerasi system